PENGEMBANGAN SISTEM PENGELOLAAN PENDAPATAN SEWA DI LKP TARI NATYA LAKSHITA - Novianto Hariwibowo, Ignatius; Yuliana, Regina (Jurnal Abdimas Musi Charitas, 2022)
This paper aims to help provide a solution to the recording of financial records that occurred at LKP Tari Natya Lakshita. This paper was conducted by analyzing the existing income structure in the studio. This research was made using a report format that has been developed into a more structured system. This paper focuses on developing a revenue management system from Microsoft Excel into an application that can facilitate companies in storing, recording, and evaluating company financial data. The result of this paper is an application system design for managing costume rental income which can be a reference in making a financial system for Natya Lakshita Dance LKP.